A35 An altered metabolism of nucleotides leads to huntington's disease related cardiomyopathy. (September 2018) - Toczek, Marta; Zielonka, Daniel; Marcinkowski, Jerzy T; Isalan, Mark; Smolenski, Ryszard T; Mielcarek, Michal
Abstract : Huntington's disease (HD) is mainly thought of as a neurological disease, but multiple epidemiological studies have demonstrated a number of cardiovascular events leading to heart failure in HD patients. Metabolic remodelling is a typical feature of the failing heart, with reduced activities of high energy phosphate generating pathways. In this study, we sought to identify metabolic abnormalities leading to HD-related cardiomyopathy in pre-clinical and clinical settings. We found that HD mouse models developed a profound deterioration in cardiac energy equilibrium, despite AMP-activated protein kinase hyperphosphorylation. This was accompanied by a reduced glucose usage and a significant deregulation of genes involved in de novo purine biosynthesis, in conversion of adenine nucleotides, and in adenosine metabolism. We established a lower enzymatic activity of enzymes involved in a degradation of cardiac nucleotides and an increased capacity for adenosine deamination. Consequently, we observed increased levels of nucleotide catabolites such as inosine, hypoxanthine, xanthine and uric acid, in murine and human HD serum. Our study suggests that future therapies should target cardiac mitochondrial dysfunction to ameliorate energetic dysfunction.